Investigation Of Rota Virus In Dogs: Feras N.Hamdaan,Ibtesam K. Hassan ans Saleem A.Hasso - Hamdaan, Feras N. (The Iraqi Journal of Veterinary Medicine, 2007)
397 fecal samples were collected from dogs of different breeds, ages andsex. Detection of rotavirus was achieved by two techniques latexagglutination test and agar gel diffusion test. Blood samples werecollected to study various hematological parameters.The results showed that 95 samples were positive to rotavirus 23samples (24.2%) were from diarrheic cases and 72 samples (75.8%)were from non diarrheic cases.Younger dogs were more affected with rotavirus infection 17 positivecases than older ages 6 positive cases. The results showed that diarrheiccases caused by rotavirus were 23 cases (25.3%) that were less than thediarrheic cases caused by other agents 68 cases (74.7%).It had been shown that the ages less than one year (11 cases) were moreaffected with rotavirus and complication with dehydration than agesolder than one year (2 cases).It was found that the morbidity rate in males (53%) was significantlyhigher than females (47%).The Terrier breed showed a high morbidity rate 42% than others Mixed,Greatdane, Goledretriver and Doberman.Our study showed that latex agglutination test was more sensitive thanagar gel diffusion test and the positive samples out of 200 samples weredetected by using latex agglutination test were 39 samples while 18positive samples by agar gel diffusion test.There were no differences in blood parameters of the dogs that showedpositive results of rotavirus in comparing them with the negativeresults.The study showed that rotavirus is widely spreaded among doges withgastrointestinal diseases, it showed that latex agglutination test is morereliable for quick clinical diagnosis.